Mean platelet volume as a predictor of clinical outcomes in patients of acute myocardial infarction - Madavi, Tejas; Bhole, Pragati; Holay, M. P. (International Journal of Research in Medical Sciences, 2019)
Background: High levels of mean platelet volume (MPV), as an indicator of larger, more reactive platelets resulting from an increased platelet turnover, may represent a risk factor for overall vascular mortality and other cardiovascular events, including myocardial infarction (MI). The present study was undertaken to see the predictive value of MPV in accessing the clinical outcomes in acute myocardial infarction, (AMI). Methods: Total consecutive 114 cases of AMI admitted to intensive care unit were enrolled in the study and were compared with the equal number of age and gender-matched controls. The clinical evaluation of cases was done at admission and on day 7 in terms of a) Cardiogenic shock, b) Arrhythmia and c) Effect of thrombolysis. Patients were classified according to tertile of baseline MPV. Results: The mean age of cases was 55.56±12.19 years. Males (66.67%) were outnumbering females (33.33%) in cases and controls showing male to female ratio of 2:1. Mean MPV was 10.2±1.27fl in cases and 7.26±0.79fl in controls which was statistically significant. Correlation of MPV with cardiogenic shock, arrhythmia and mortality was significant. Correlation of MPV with risk factor shows that diabetes was the only risk factor significant in AMI. Multiple logistic regression of risk factors with mortality in AMI shows that high MPV and obesity was found to be independently associated with mortality in AMI. Conclusions: Mean platelet volume is simple, easily available and cheap method. Serial estimation of MPV is a predictor of adverse clinical outcome in AMI so treating doctor can be more vigilant.